Water Services in Chile : Comparing Private and Public Performance - Bitrán, Gabriel A. (World Bank, Washington, DC, 2012)
In 1988, Chile put in place a new regulatory regime for water and sanitation, allowing rates to reflect the actual cost of providing services. The government then reorganized the sector under 13 state-owned regional water companies and, in 1998, started to partially privatize some of them. Four years after the first sale, it is now possible to assess the early results of privatization. This Note examines the outcomes for investors, and consumers, and compares the performance of the privatized companies with that of companies remaining under state ownership.